2005
DOI: 10.1152/japplphysiol.01422.2004
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of human vaginal oxygen and carbon dioxide levels during and post menses

Abstract: Previous in vitro and in vivo animal studies showed that O(2) and CO(2) concentrations can affect virulence of pathogenic bacteria such as Staphylococcus aureus. The objective of this work was to measure O(2) and CO(2) levels in the vaginal environment during tampon wear using newly available sensor technology. Measurements by two vaginal sensors showed a decrease in vaginal O(2) levels after tampon insertion. These decreases were independent of the type of tampons used and the time of measurement (mid-cycle o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 34 publications
4
45
0
Order By: Relevance
“…As noted previously, blood components, and more specifically hemoglobin peptides, negatively affect production of TSST-1 (147). The introduction of oxygen into the human vagina, a typically anaerobic environment, by tampons is now considered the major reason for the tampon association with mTSS (84,168,169). The introduction of oxygen would also explain the major association of mTSS with higher-absorbency tampons in that those tampons introduce more oxygen.…”
Section: Staphylococcal Menstrual Tssmentioning
confidence: 89%
“…As noted previously, blood components, and more specifically hemoglobin peptides, negatively affect production of TSST-1 (147). The introduction of oxygen into the human vagina, a typically anaerobic environment, by tampons is now considered the major reason for the tampon association with mTSS (84,168,169). The introduction of oxygen would also explain the major association of mTSS with higher-absorbency tampons in that those tampons introduce more oxygen.…”
Section: Staphylococcal Menstrual Tssmentioning
confidence: 89%
“…During menstruation, the vaginal pH becomes neutral, most likely due to the influx of menses blood, which has a pH range of 6.9 to 7.2 (6). In addition, menses blood in the vagina also results in an elevated protein concentration (6) and an increase in oxygen and carbon dioxide concentrations (27), which all contribute to the production of TSST-1 by S. aureus (43,78).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it is well established that the in vitro environmental conditions that favor TSST-1 production can be present vaginally in menstruating women (10,12,25,33). However, only a single study has shown that TSST-1 can be produced vaginally (22).…”
Section: Discussionmentioning
confidence: 99%
“…We also have demonstrated that sections of tampons that have a low hemoglobin density contain serum proteins at about 1% of the level of those found in blood (unpublished data). The other major factor thought to be necessary for TSST-1 production is the presence of an aerobic environment, and we have previously established that such an environment is present vaginally through the oxygen in menstrual blood as well as through the inherent oxygen in tampons (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation